2015
DOI: 10.1159/000375410
|View full text |Cite
|
Sign up to set email alerts
|

Urinary C-Peptide/Creatinine Ratio Can Distinguish Maturity-Onset Diabetes of the Young from Type 1 Diabetes in Children and Adolescents: A Single-Center Experience

Abstract: Background: The urinary C-peptide/creatinine ratio (UCPCR) and fasting C-peptide level can assess beta-cell function in clinical practice. In the present study, the use of the UCPCR and fasting C-peptide levels was investigated in the differential diagnosis between maturity-onset diabetes of the young (MODY) and type 1 diabetes mellitus (T1DM). Methods: Twenty-seven patients with genetically confirmed MODY by next-generation sequence analysis and 42 children with T1DM were included. C-peptide levels were measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 22 publications
0
21
0
Order By: Relevance
“…Yılmaz Ağladıoğlu et al [24] used UCPCR to differentiate MODY from type 1 diabetes in a pediatric group of patients diagnosed at least 2 years earlier. They reported that at a level of 0.22 nmol/mmol, UCPCR exhibited 96.3% sensitivity and 85.7% specificity for identifying cases of MODY.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yılmaz Ağladıoğlu et al [24] used UCPCR to differentiate MODY from type 1 diabetes in a pediatric group of patients diagnosed at least 2 years earlier. They reported that at a level of 0.22 nmol/mmol, UCPCR exhibited 96.3% sensitivity and 85.7% specificity for identifying cases of MODY.…”
Section: Discussionmentioning
confidence: 99%
“…Values of 0.2 nmol/mmol or above were shown to be 97% sensitive and 96% specific for differentiating HNF1A and HNF4A cases from type 1 diabetes [7]. We adopted the UCPCR value used by this study because of its high sensitivity combined with high specificity [24, 25]. …”
Section: Discussionmentioning
confidence: 99%
“…This test was reported to have sensitivity up to 93% and specificity up to 90% for discriminating between MODY and T1DM. [44] MODY 1 HNF-4a regulates transcription of the insulin gene and other genes that are involved in glucose metabolism. If HNF-4a function is decreased then it affects the b-cells mainly by controlling HNF1a which is also a transcription factor for insulin.…”
Section: Mody Features and Diagnosismentioning
confidence: 99%
“…The UCPCR provides another measure for beta-cell function in clinical practice [28]. In the Study by Yılmaz Agladioglu et al [29], the use of the UCPCR and fasting C-peptide levels was investigated in the differential diagnosis between MODY and T1DM. T1DM subjects received insulin treatment and had been diagnosed with diabetes for at least 2 years.…”
mentioning
confidence: 99%
“…Biochemical markers of C-peptide and 24-hour urinary C-peptide add to the understanding of markers of diagnosis consistent with current theories of the pathogenesis of diabetes. The paper by Yılmaz Agladioglu et al [29] suggests that UCPCR and fasting C-peptide testing after 2 years of diagnosis in children and adolescents is able to distinguish patients with MODY from patients with T1DM with a high specificity and sensitivity. Further studies in larger samples with a wider distribution of patients with specific MODY mutations are indicated.…”
mentioning
confidence: 99%